Artistic Imagery in the Poetry of Ibn Rashīq al-Misīlī: An Analytical Study – The Poem of Lightning - mehcer, warda (El Omda in Linguistics and Discourse Analysis, 2018)
This article analyzes the artistic imagery in the poetry of Ibn Rashīq, focusing on a single poem selected for its relevance. It serves as the subject for studying his artistic imagery and pictorial poetic techniques, which have been addressed by critics in previous studies but were nearly overlooked by the poet himself despite his mastery.